(untitled) (Journal of Civil Engineering Researchers, 2022)
Due to the widespread use of concrete in all kinds of structures, the probability of its exposure to dynamic loads has increased. Since concrete is one of the most widely used materials in civil engineering, its main weakness can be pointed out, which is its brittleness and brittle performance. The use of fibers to improve the properties of concrete has been the focus of engineers for a long time. The most common fibers used to increase the impact resistance of concrete, steel and polypropylene were investigated in this research as single and hybrid fibers. In this study, by using the ACI 544-based weight projection method, the resistance of concrete against impact loading on standard cylindrical concrete samples (30 x 15) containing steel fibers and polypropylene in two cases with and without lap sheet FRPs were investigated. The results showed that the use of these fibers increases the impact resistance of concrete. Also, both CFRP and GFRP sheets that were tested improve the impact resistance of concrete and increase the number of cycles of this test. Some GFRP sheets have performed better than CFRP. Also, the presence of FRP sheets has caused a change in the type of failure compared to the absence of FRP. Also, concrete samples whith fiber delay concrete breaking, significantly.